2016
DOI: 10.1364/oe.24.008290
|View full text |Cite
|
Sign up to set email alerts
|

High-bandwidth uni-traveling carrier waveguide photodetector on an InP-membrane-on-silicon platform

Abstract: Abstract:A uni-traveling carrier photodetector (UTC-PD), heterogeneously integrated on silicon, is demonstrated. It is fabricated in an InP-based photonic membrane bonded on a silicon wafer, using a novel double-sided processing scheme. A very high 3 dB bandwidth of beyond 67 GHz is obtained, together with a responsivity of 0.7 A/W at 1.55 µm wavelength. In addition, open eye diagrams at 54 Gb/s are observed. These results promise high speed applications using a novel full-functionality photonic platform on si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 24 publications
0
55
0
Order By: Relevance
“…Now, LNOI offers a similar optical integration density, which makes the development of photodetectors for LNOI waveguides attractive. This means that many of the well‐established heterogeneous integration fabrication capabilities of III‐V photodetectors on silicon based platforms should be transferable to LNOI waveguides . Such heterogonous photodetectors are very attractive as they can have high bandwidths, such as the recent demonstration of 65 GHz bandwidth high‐power photodetectors .…”
Section: Photonic Building Blocks In Lnoimentioning
confidence: 99%
“…Now, LNOI offers a similar optical integration density, which makes the development of photodetectors for LNOI waveguides attractive. This means that many of the well‐established heterogeneous integration fabrication capabilities of III‐V photodetectors on silicon based platforms should be transferable to LNOI waveguides . Such heterogonous photodetectors are very attractive as they can have high bandwidths, such as the recent demonstration of 65 GHz bandwidth high‐power photodetectors .…”
Section: Photonic Building Blocks In Lnoimentioning
confidence: 99%
“…It is therefore essential to design the device in a platform that can achieve a high overlap of this thin layer with the optical mode. The IMOS platform also allows for the double-sided processing that is needed to create the structure proposed below [11]. Since IMOS aims for integration of photonics with advanced CMOS electronics, we take the available voltage swing to be 1.5 V.…”
Section: Eam Operation and Designmentioning
confidence: 99%
“…Using an impact ionization model [19] that includes the dead space effect [20] we estimate the breakdown voltage due to avalanche current to be −8 V. The band-to-band tunneling current for the proposed modulator is predicted to be well below 3 mA [12]. In the past we have found that currents higher than 3 mA caused thermal damage to a uni-traveling-wave photodetector (UTC PD, described in [11]). As the modulator proposed here will have a surface area larger than that of the UTC PD, we can assume that no thermal damage will occur.…”
Section: A Electron Density Profile From Semiconductor Simulationmentioning
confidence: 99%
“…3(a)) [8]. By using electrons with a high drift velocity as the only active carrier, the transit-time constant of the UTC-PD is as low as a few picoseconds.…”
Section: Utc-detectormentioning
confidence: 99%